Impact of Different Implant Surfaces Topographies on Peri-Implant Tissues: An Update of Current Available Data on Dental Implants Retrieved from Human Jaws - A. Shibli, Jamil; T. Pires, Jefferson; Piattelli, Adriano; Iezzi, Giovanna; Mangano, Carlo; Mangano, Francesco; L.S. de Souza, Sergio; A. Gehrke, Sergio; Wang, Hom-Lay; M. Dohan Ehrenfest, David (Current Pharmaceutical Biotechnology, 2017)
The high success range obtained with the implant-supported restorations has improved its applicability on routine of the daily clinical practice. This elevated percentage of success is related to the previous pre-clinical data obtained from animal and in vitro studies that evaluated the impact of implant surface topographies on bone tissue. However, the histological evaluation of human bone tissue is scarce. Therefore, the aim of this review is to depict an actual panorama of the data available on boneto- implant contact (BIC) of retrieved implants from human jaws. Some aspects of implant surface topography as well as systemic conditions as osteoporosis and smoking habit were demonstrated to have a strong impact, suggesting that the data obtained from human bone tissue is still valuable for the better understanding of the osseointegration process. This article also highlighted that most data in humans are difficult to interpret, due to the lack of detailed information about the surfaces found in retrieved implants. Without the definition of the surface characteristics, it is difficult to link exactly the surface patterns to specific clinical observations, and all observations remain de facto incomplete. As a conclusion, data from implants retrieved from human jaws are very important for our understanding, however the studies remain scarce and data is fragmented. This important approach should be improved, completed and developed in the future.
Keywords: human histology